Systematic Literature Review: The Effect of Quality of Work-Life Balance and Corporate Culture on Employee Engagement - Akhirudin Akhirudin; Bambang Moertono Setiawan; Nur Wening; Sujoko Sujoko (Jurnal Indonesia Sosial Sains, 2024)
Employees are one of the entities that are quite vital in driving a company. They are required to contribute concretely, optimally and continuously quantitatively and qualitatively in daily operations in order to achieve company goals. To support employees to remain enthusiastic and focused on company goals, a conducive and quality work environment is needed so that employees feel comfortable and will continue to be engaged (engaged) with the company. This study aims to determine the extent to which work life balance Employees are one of the entities that are quite vital in driving a company. They are required to contribute concretely, optimally and continuously quantitatively and qualitatively in daily operations in order to achieve company goals. To support employees to remain enthusiastic and focused on company goals, a conducive and quality work environment is needed so that employees feel comfortable and will continue to be engaged (engaged) with the company. This study aims to determine the extent to which work life balance and work culture influence employee engagement. The method used in this research is systematic literature review (SLR) of journal articles published in 2017-2022. Based on the results of literature analysis on the 5 selected journals, it shows that the independent variables, namely quality of work life and organizational culture, have an effect on employee engagement. This study seeks to determine and prove the extent to which the variables of quality of work life and organizational culture influence employee engagement, and based on the results of the study using a systematic literature review, it can be concluded: Quality of work life influences the company's employee engagement, Company culture also influences company employee engagementand work culture influence employee engagement. The method used in this research is systematic literature review (SLR) of journal articles published in 2017-2022. Based on the results of literature analysis on the 5 selected journals, it shows that the independent variables, namely quality of work life and organizational culture, have an effect on employee engagement. This study seeks to determine and prove the extent to which the variables of quality of work life and organizational culture influence employee engagement, and based on the results of the study using a systematic literature review, it can be concluded: Quality of work life influences the company's employee engagement, Company culture also influences company employee engagement